Comparative Analysis of the Performance of Ice Cream Making Machines Using Variations in Capillary Pipe Diameters - Ferry Sugara; Waluyo Djoko Yudisworo; Karsid Karsid (Mestro, 2021)
Current refigeration technology has an important influence in improving the quality of food products. The purpose of this study is to find out how much the difference in performance generated from the expansion device in the form of two capillary pipes of different diameters and know the power consumption of electricity used, so that it knows the electric power per day. The method used in this study is to test the ice cream maker refrigeration system, by testing its performance by measuring the temperature and pressure in each main component when the system is steady. The results of the actual COP value of the average capillary pipe diameter of 0.028 inches are 2.16 while the actual COP value of the average capillary pipe diameter of 0.031 inches is 2.74. And the actual COP value of a 0.028 inch diameter capillary tube has a greater value of 2.16 while a capillary pipe with a diameter of 0.031 inches has a smaller value of 1.88. Whereas the biggest value of refractive efficiency at the average value is a capillary pipe with a diameter of 0.028 inches of 63.58%. While for capillary pipes with a diameter of 0.031 inches smaller the value of refraction efficiency averaged 59.49% and the cabin temperature in capillary pipes with a diameter of 0.028 inches, the average value was -9.82 0C. While for capillary pipes with a diameter of 0.031 inches smaller it has a cooler average value of -9.09 0C.